COMPOSITES OF POLYURETHAN BASED ON PALM OIL OIL WITH FILLING MATERIALS BENTONITE-CHITOSAN AS ANTIBACTERIAL COATING ON MEDICAL EQUIPMENT - Tengku Venna MaurizaRamadhanti; Alfian Putra; Teuku Rihayat (Jurnal Sains dan Teknologi Reaksi, 2017)
Modification of polyurethane by adding fillers such as bentonite can improve the physical properties of polyurethane coatings. Polyurethane synthesis is carried out using the prepolymer method by reacting toluene diisocyanate (TDI) with palm oil based polyols. Bentonite addition is used to provide heat resistance in polyurethane coating material. The concentration of bentonite used was 1.5% b / b, 3.5% b / b, and 5.5% b / b. The resulting polyol synthesis will be analyzed using FTIR to see the OH group formed. The bentonite purification process was carried out by using cetyltrimethyl ammonium bromide in bentonite solution. The target in this study is the anti-bacterial properties of the products produced. Whereas to see the characteristics carried out SEM and FTIR analysis